Effects of nitrogen topdressing and paclobutrazol at different stages on spike differentiation and yield of winter wheat - Li,Dongxiao; Mo,Shaojing; Batchelor,William D.; Cheng,Ruiting; Wang,Hongguang; Li,Ruiqi (PeerJ, 2021)
Background Optimal nitrogen (N) application and plant growth regulators can improve wheat productivity. This can help to improve yield level and ensure food security with limited resources in the Huang-Huai-Hai Plain of China (HPC). Methods A 2-year field experiment was conducted using a randomized block design with four treatments (TS-N topdressing at pseudostem erection stage ; TPS-N topdressing combined with paclobutrazol application at pseudostem erection stage; TJ-N topdressing at jointing stage; TPJ-N topdressing at combined with paclobutrazol application at jointing stage) in 2011–2013. Results The grain number per ear, thousand kernel weight and yield for the TJ and TPJ treatments were higher than those of the TS and TPS treatments. Grain number per ear, yield, and thousands kernel weigh for the TPJ treatment were significantly higher than for the TS and TPS in 2011–2012 (9.82% and 7.27%, 10.23% and 8.99%, 6.12% and 5.58%) and in 2012–2013 (10.21% and 11.55%, 8.00% and 6.58%, 0.00 and 0.00), respectively. Thousands kernel weight under TJ were significantly higher than those under TS and TPS by 13.21% and 14.03%, respectively in 2012–2013. The floret number, significantly correlated with cytokinin content, was also significantly increased under TJ and TPJ at connectivum differentiation stage. For TPJ treatment, the floret number was significantly higher than for the TS, TPS, and TJ by 19.92%, 10.21%, 6.10% in 2011–2012; it was higher than for the TS and TPS by 28.06% and 29.61% in 2012–2013, respectively. The relative expression level of cytokinin oxidase/dehydrogenase gene (TaCKX2.2) was improved during flowering, when cytokinin content was at high level and was also inhibited by paclobutrazol with different degrees. Conclusions Therefore, nitrogen topdressing at jointing stage had increased grain number per ear, thousand kernel weight, and grain yield of wheat. Paclobutrazol could delay spike differentiation and promote cytokinin accumulation that induced expression of TaCKX2.2, maintaining hormonal balance and affecting wheat spike morphogenesis.
Keywords: Topdressing stages; Floret number; Phytohormone; Spike differentiation; TACKX2.2